Kebijakan Kurikulum Merdeka Belajar Guna Meningkatkan Prestasi Belajar Peserta Didik - Marpaung, Wardatun Thaibah; Hasanah, Uswatun; Lubis, Melati Br; Maulida, Sifa; Darmansyah, Tengku (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the Independent Learning Curriculum policy in improving student learning achievement. The study uses a literature study method, which involves collecting and analyzing data from various library sources, such as books, journals, scientific articles, and policy documents. The sub-discussion of this study includes the definition of the Independent Curriculum education policy and the concept of student learning achievement. The Independent Curriculum is designed to provide freedom for schools and educators in determining learning strategies that are appropriate to the needs and potential of students. This policy emphasizes project-based learning, curriculum flexibility, and strengthening the Pancasila Student profile. Student learning achievement is defined as the achievement of learning outcomes that include cognitive, affective, and psychomotor aspects in accordance with educational objectives. The results of the analysis show that the Independent Curriculum policy can improve student learning achievement by providing wider exploration space, developing creativity, and strengthening critical thinking skills. However, the implementation of this policy requires support from various parties, including educators, policy makers, and parents of students, as well as adequate training for teachers. This study concludes that the Independent Learning Curriculum is a relevant policy to improve the quality of education and student learning achievement, as long as it is implemented consistently and comprehensively.